2016
DOI: 10.1111/jce.12901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Remote Magnetic Irrigated Tip Ablation versus Manual Catheter Irrigated Tip Catheter Ablation With and Without Force Sensing Feedback

Abstract: and contact force (CF) sensing technologies have been utilized in an effort to improve safety and efficacy of catheter ablation. A comparative analysis of the relative short-and long-term outcomes of AF patients has not been performed. As such, we comparatively evaluated the safety and efficacy of these technologies.Methods: A total of 627 patients who underwent catheter ablation with either a manual irrigated tip catheter: (312, 49.8%) or by RMN: (315, 50.2%) were included in this single-center cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…A similar distribution of EGM morphologies between the two groups was found before RF applications, suggesting a similar orientation of the catheters on the tissue with both technologies . Our results are in line with a recent comparative study between RMN and CF‐guided AF ablation . Natale et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar distribution of EGM morphologies between the two groups was found before RF applications, suggesting a similar orientation of the catheters on the tissue with both technologies . Our results are in line with a recent comparative study between RMN and CF‐guided AF ablation . Natale et al .…”
Section: Discussionsupporting
confidence: 93%
“…18 Our results are in line with a recent comparative study between RMN and CF-guided AF ablation. 19…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and prospective cohort studies have shown that RMN‐guided ablation of AF was associated with low complication rates and comparable long‐term freedom from AF when compared to manual ablation 22–24,26 21 …”
Section: Outcomes With Robotic‐assisted Catheter Ablationmentioning
confidence: 99%
“…Despite numerous publications showing reductions in fluoroscopic exposure and the obvious benefits of not wearing lead and standing tableside for hours, remote magnetic navigation has not become the standard of care in the world [4]. Most publications appear to show similar success rates, and many show favorable complication rates [5][6][7]. So what is the limitation to universal acceptance?…”
mentioning
confidence: 99%
“…This limitation also makes manual catheter contact force in certain areas inconsistent or suboptimal, which may also result in insufficient ablation lesions. Maps obtained via magnetic navigation tend to have less distortion and more accurately represent the chamber of interest [5,8]. The more uniform and constant contact may also improve the ablation lesions.…”
mentioning
confidence: 99%